Catching up, structural transformation, and inequality: Lessons from Asia - Bruno Martorano; Donghyun Park; Marco Sanfilippo (Asian Development Bank (ADB), 2016)
While structural transformation, driven by technological progress, productivity growth, and capital deepening, has contributed to Asia's sustained rapid growth, its effect on income inequality is uncertain. The central objective of our paper is to empirically examine the effect of structural change on wage inequality in Asia, using industry-level data for three skill groups of workers. Our evidence indicates that structural change, pushed by productivity catch-up with advanced economies, capital deepness, and the shift of the economic structures to more skill-intensive industries, has exacerbated inequality in the region. However, we also find that policy responses, especially investment in education matching the higher demand for skills and competitive exchange rates, can mitigate the increase in inequality.
Keywords: E24; L16; 330; Asia; inequality; productivity; structural change; wage gap